The Implementation of Role Playing Learning Model to Increase Student Learning Activities and Outcomes - Prayitno, Putra Hilmi; Wibowo, Agus (Unversitas Negeri Malang, 2017)
This present research was conducted in the SMA Laboratorium Universitas Negeri Malang. 45 students from XI class of Social Science 1 were recruited as the subject of this research. This research includes classroom action research consisting of two cycles and each cycle consists of two meetings. The data for student learning activities are collected by using observation sheets, meanwhile, the data for student learning activities to learning outcomes are collected by observing the score progress in the test cycle I and cycle II. The objective of this study are; 1) To describe and analyze the use of role-playing learning model in improving students activity of XI class SMA Laboratorium Universitas Negeri Malang in economic subjects, and 2) To observe the student’s activity and poor students' in economic subjects after implementing the Role Playing learning model. In this research, student learning activities increased from 46.67% in the first cycle to 73.33% in the second cycle. Meanwhile, the learning outcomes increased from 73.3% to 77.8% in cycle II. It can be concluded that role-playing learning model increased the learning activity and outcome of the XI social science class 1 of SMA Laboratorium Universitas Negeri Malang. Keywords: role-playing learning models, student learning activities, learning outcomes DOI: 10.17977/um013v1i22017p073